Apología de la métrica - Torre, Esteban (Rhythmica. Revista Española de Métrica Comparada, 2020)
La métrica, como ciencia del verso, ha sido en ocasiones objeto de menosprecio y controversia por parte de los poetas, los profesores de literatura y los propios teóricos de esta ciencia. En el presente trabajo se lleva a cabo una detenida defensa y alabanza de las formas métricas, que se consideran como parte sustancial e imprescindible de la poesía. Metrics, as a science of verse, has, at certain times, been the target of disparagement and controversy on the part of poets, of teachers of literature, and even of the theorists of this very science. In this present study, what is undertaken is a heedful defense and appreciation of metric forms which are deemed to be a substantial and essential component of poetry.